Sampling Plan Using Process Loss Index Using Multiple Dependent State Sampling Under Neutrosophic Statistics - Muhammad Aslam; Muhammad Azam; Mohammed Albassam (IEEE Access)
This paper presents the designing of a sampling plan using the process loss consideration for the multiple dependent state sampling under the neutrosophic statistics. The operating characteristics under the neutrosophic statistical interval method (NSIM) are developed to find the neutrosophic plan parameters of the proposed sampling plan. A non-linear optimization under NSIM is used to find the optimal neutrosophic plan parameters under the given conditions. The advantages of the proposed sampling plan are discussed over the existing sampling plans. A real example having some uncertain observations is given for the illustration purpose.